Criterion for elastoplastic failure of bimetallic plate with edge crack of transverse shear at the boundary of the materials joint - Kurguzov, Vladimir Dmitriyevich; Fedorova, Natal’ya Vitaliyevna (Computational Continuum Mechanics, 2021)
The initiation of a transverse shear edge crack in elastoplastic materials with the limiting strain is considered. The crack propagation criterion is formulated using a modified Leonov-Panasyuk-Dugdale model using the additional parameter - the width of the plasticity zone. The coupled quasi-brittle fracture criterion for mode II cracks in an elastoplastic material is formulated under conditions of small-scale yield in the presence of a singular feature of the stress field in the vicinity of the crack tip. The coupled fracture criterion includes the deformation criterion, which is formulated at the crack tip, as well as the force criterion, which is formulated at the model crack tip. The lengths of the initial and model cracks differ by the length of the prefracture zone. The sequential analysis of the possibility of applying the proposed fracture criterion in determining the critical loads for solids containing edge cracks of transverse shear at the interface of different media is performed. Quasi-brittle fracture diagrams are constructed for a composite plate with an edge crack under plane strain and plane stress conditions. he analysis of the parameters included in the proposed model of quasi-brittle fracture is carried out. The model parameters are proposed to be selected by approximation of simple shear diagram and critical stress intensity factor. The critical loads were found numerically for the quasi-ductile and ductile fracture types. The finite element method is used to solve the problem of drawing out a reinforcing layer from a metal composite under quasi-static loading. The process of propagation of plastic zones in the vicinity of the crack tip is described consistently. It is shown that the shapes of the constructed plastic zones differ significantly from the well-known classical concepts.
Keywords: brittle, quasi-brittle, quasi-tough and ductile fracture; elastoplastic materials; ultimate deformation